2014
DOI: 10.1002/14651858.cd007049.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Wound infiltration with local anaesthetic agents for laparoscopic cholecystectomy

Abstract: Serious adverse events were rare in studies evaluating local anaesthetic wound infiltration (very low quality evidence). There is very low quality evidence that infiltration reduces pain in low anaesthetic risk people undergoing elective laparoscopic cholecystectomy. However, the clinical importance of this reduction in pain is likely to be small. Further randomised clinical trials at low risk of systematic and random errors are necessary. Such trials should include important clinical outcomes such as quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 68 publications
0
37
0
6
Order By: Relevance
“…Local 69 and regional 70 anaesthesia has shown benefit in laparoscopic appendicectomy, but evidence does not support a preference of administration of local anaesthetic prior to skin incision (pre-emptive analgesia) versus at the end of laparoscopy. 71 Patient-controlled analgesia appears beneficial in perforated appendicitis 72 but increases opiate use and pruritis, 73 which could delay discharge after uncomplicated appendicitis. Four prospective non-randomized studies [74][75][76][77] and three retrospective studies [78][79][80] have shown same day discharge or 'outpatient' appendectomy to be feasible and safe in contrast to the 3-week convalescence of patients at the turn of the previous century.…”
Section: Modern Recoverymentioning
confidence: 99%
“…Local 69 and regional 70 anaesthesia has shown benefit in laparoscopic appendicectomy, but evidence does not support a preference of administration of local anaesthetic prior to skin incision (pre-emptive analgesia) versus at the end of laparoscopy. 71 Patient-controlled analgesia appears beneficial in perforated appendicitis 72 but increases opiate use and pruritis, 73 which could delay discharge after uncomplicated appendicitis. Four prospective non-randomized studies [74][75][76][77] and three retrospective studies [78][79][80] have shown same day discharge or 'outpatient' appendectomy to be feasible and safe in contrast to the 3-week convalescence of patients at the turn of the previous century.…”
Section: Modern Recoverymentioning
confidence: 99%
“…9 A Cochrane review was published in 2014 in the wiley online library, reviewing a total of 26 papers on grounds of wound infilitration with local anaesthetics for laparoscopic cholecystectomies. 10 In the review, the authors have concluded that serious adverse events were rare in studies evaluating local anaesthetic wound infiltration (very low quality evidence). There is very low quality evidence that infiltration reduces pain in low anaesthetic risk people undergoing elective laparoscopic cholecystectomy.…”
Section: Vas Scoresmentioning
confidence: 99%
“…In patients undergoing elective laparoscopic cholecystectomy, the optimal method of reducing postoperative pain has not been established and it is likely there would be major differences between elective laparoscopic cholecystectomy and acute choleystitis. The overall evidence from RCTs examining the role of wound infiltration or intraperitoneal instillation with a local anaesthetic and the role of systemic pharmacologic agents in reducing postoperative pain after elective laparoscopic cholecystectomy is of low quality [63][64][65].…”
Section: The Optimal Analgesia For Managing Patients With Acute Cholementioning
confidence: 99%